Report on a portion of Conrad and Whitehorse mining districts, Yukon [electronic resource] - Cairnes, D. D. (DeLorme Donaldson), 1879-1917.; Geological Survey of Canada. (Ottawa : S.E. Dawson, 1908)
Tables. At head of title: Canada. Department of Mines, Geological Survey Braanch . Electronic reproduction. Mode of access: Internet. 44